Real-Space Visualization of Energy Loss and Carrier Diffusion in a Semiconductor Nanowire Array Using 4D Electron Microscopy - Bose, Riya (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.